A contribution to the checklist of fishes of San Luis province, Argentina - Cardoso, Yamila Paula (2015)
San Luis province presents arheic and endorheic basins that are poorly understood in terms of their ichthyological composition. The samples taken recently from the main basins of this province have yielded data of undisputed biogeographic value for the knowledge of the ichthyofauna of San Luis, as well as for drawing up lists of species for watersheds with poor or absent previous records. Here, we cite Jenynsia multidentata from the Desaguadero and Bebedero rivers, Cnesterodon decemmaculatus for Chorrillos River, and Oligosarcus jenynsii for Luján, Quines and Quinto rivers. We add five taxa to the Nogolí River that have not been previously reported. We also present for the first time a list of the fish fauna from the Conlara, Luján and Quines basins. Our results provide 34 new records of freshwater fish distribution.